Expression of HIV-1 subtype CRF01_AE GP41 protein in E. coli and its application for detection of anti-HIV antibody in patient’s sera by Western blot and ELISA - Quỳnh, Bạch Thị Như; Hiền, Vũ Thị; Thu, Hà Thị; Hoa, Nguyễn Thị; Hằng, Lê Phương; Tùng, Nguyễn Thanh; Bắc, Nguyễn Xuân; Quyền, Đồng Văn; Phủng, Lê Văn; Kháng, Đinh Duy (Vietnam Journal of Biotechnology, 2012)
In this paper we report the results on expression and purification of envelop GP41 protein of HIV-1 subtype CRF01_AE and its application for detection of anti-HIV antibody in patient’s sera by Western blot and ELISA. A gene region coding for extracellular domain of GP41 protein was amplified by PCR, inserted into pET32a+ expression vector. The recombinant plasmid carrying gp41 gene were selected by restriction enzyme analysis and confirmed by DNA sequencing. As designed, the recombinant GP41 protein was fused to a 6 histidines and Theoredoxin (Trx) at its N-terminal and has a molecular mass of approximately 37 kDa (6His-Trx-GP41). Recombinant GP41 was expressed as soluble form at 30oC and 0.5 mM IPTG with the expression yield of 20 mg/l culture medium. The recombinant protein was purified by affinity chromatography using ProBond Nickel-Chelating Resin (Invitrogen) under native condition, and was then used to detect anti-HIV antibody in patient’s sera by Western blot and ELISA. The Western blot results showed that recombinant GP41 reacted specifically with the antibody in HIV patient’s sera, especially it reacted more strongly with antibodies against HIV subtype CRF01_AE than that of HIV-1 subtype B. This data suggests the importance of development of HIV diagnostic kits base on antigens derived from subtypes circulating in the country.